Sulphur-containing amino acids promote the expression of CG33474 and its neighbouring genes through the transsulphuration pathway. - Xu, L.; Liu, M.; He, L. (Fly, 2026)
Sulphur-containing amino acids (SAAs), including methionine and cysteine, play crucial roles in antioxidant defence, anti-ageing, cytoprotection, and anti-inflammatory responses. Previous studies have shown that SAAs promote peroxisome elevation and fat loss by inducing the expression of the peroxisome-related gene CG33474 in the Drosophila fat body. However, the underlying regulatory mechanism remains unclear. In this study, we demonstrated that the transsulphuration pathway contributes to CG33474 induction, as supplementation with specific downstream metabolites of this pathway recapitulates this effect. Moreover, we found that SAAs upregulate not only CG33474 but also several neighbouring genes - including CG11825, Prx2540-1, Prx2540-2, and CG12896 - suggesting coordinated regulation within this genomic locus. Through fluorescence reporter assays, we discovered that a ~1 kb genomic region upstream of CG33474 harbours the cis-regulatory element mediating SAA responsiveness and that this responsiveness is fat body-specific. Finally, our data suggest that induction of CG33474 may play a role in resistance to different stresses and in regulating ageing as fat body-specific overexpression of CG33474 significantly extends lifespan in Drosophila. Together, our findings reveal that SAAs modulate the expression of CG33474 and its adjacent genes through the transsulphuration pathway, providing an additional mechanistic basis for the antioxidant effects of SAAs.